2004
DOI: 10.1007/s00299-003-0728-0
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of stilbenes in in vitro bioassays and in transgenic Populus expressing a gene encoding pinosylvin synthase

Abstract: The effect of two stilbene compounds, pinosylvin and resveratrol, on the growth of several fungi was evaluated in plate tests. Wood decay tests were carried out with birch and aspen samples impregnated with the two stilbenes. In plate experiments, resveratrol had an enhancing effect on growth at concentrations where pinosylvin was already enough to prevent the growth of most fungi studied. Pinosylvin impregnated at 0.2% (w/w) concentration significantly reduced the decay caused by all fungi except Phellinus tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 28 publications
(23 reference statements)
2
55
0
1
Order By: Relevance
“…In general, pathogens are likely to be highly adapted to the quality and quantity of phenolics of their hosts. For instance, Seppänen et al (2004) showed that decay fungi of deciduous trees were more sensitive in vitro to high concentrations of PS, compared with decay fungi of conifers. However, Pyrenopeziza betulicola, a birch leaf spot pathogen, was relatively tolerant to PS (Seppänen et al 2004).…”
Section: Antifungal Activity Of Phenolic Metabolites (In Vitro Effects)mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, pathogens are likely to be highly adapted to the quality and quantity of phenolics of their hosts. For instance, Seppänen et al (2004) showed that decay fungi of deciduous trees were more sensitive in vitro to high concentrations of PS, compared with decay fungi of conifers. However, Pyrenopeziza betulicola, a birch leaf spot pathogen, was relatively tolerant to PS (Seppänen et al 2004).…”
Section: Antifungal Activity Of Phenolic Metabolites (In Vitro Effects)mentioning
confidence: 99%
“…For instance, Seppänen et al (2004) showed that decay fungi of deciduous trees were more sensitive in vitro to high concentrations of PS, compared with decay fungi of conifers. However, Pyrenopeziza betulicola, a birch leaf spot pathogen, was relatively tolerant to PS (Seppänen et al 2004). Differences in sensitivity-tolerance are likely to be explained by the differences in the array and activity of enzymes among fungi.…”
Section: Antifungal Activity Of Phenolic Metabolites (In Vitro Effects)mentioning
confidence: 99%
“…It has been shown that the introduction of STSs into non-stilbene-producing species such as poplar (Seppänen et al, 2004), wheat (Serazetdinova et al, 2005), and alfalfa (Hipskind and Paiva, 2000) led to increased fungal resistance. However, it was unclear whether increased stilbene levels in spruce, which already produces a basal level of these compounds, would also lead to increased resistance against the bark beetle-associated fungus C. polonica.…”
Section: Stilbene Biosynthesis In Spruce Is a Defense Mechanism Againmentioning
confidence: 99%
“…Stilbenes have also been shown to exhibit antifungal activity in non-stilbene-producing species such as poplar (Populus spp. ; Seppänen et al, 2004), wheat (Triticum aestivum; Serazetdinova et al, 2005), and alfalfa (Medicago sativa; Hipskind and Paiva, 2000) when they were introduced by genetic engineering. These compounds inhibit fungal growth by interfering with microtubule assembly (Woods et al, 1995), disrupting plasma membranes, and uncoupling electron transport in fungal spores and germ tubes (Pezet and Pont, 1990).…”
mentioning
confidence: 99%
“…Genetic transformation of poplar draws attention for growth fastening [6,7], decrease of lignin content [8][9][10], and increase of the resistance to pests [11]. This transformation is facilitated due to the fact that the genome of poplar is fully sequenced in recent time [12,13] and now it is considered as a model for the study of molecular biology of woody plants [14].…”
Section: Introductionmentioning
confidence: 99%